Waste 4.0: transforming medical waste management through digitalization and automated segregation - Mohamed, Nurul Hamizah; Khan, Samir; Jagtap, Sandeep (Springer, 2024)
Medical waste management is a crucial issue due to its potential health risks to humans and harm to the environment. The World Health Organization (WHO) advises separating medical waste into seven groups based on its type. However, despite the implementation of color-coded bin bags, cases of missegregation still occur frequently, leading to injuries and spreading diseases. Infectious waste such as sharps, human tissue, and body parts are often found mixed in waste bins, posing a severe threat to waste employees. To address this issue, this paper proposes exploring the potential of digitalization in waste segregation. The literature on current segregation methods and technology applications is analysed and compared, and a framework for utilizing barcode tagging and scanning to ensure waste is correctly categorized is presented. The barcodes and scanner will be connected through a monitoring system, which can notify waste generators and collectors of misplacing or mixed waste. This digitalization system is expected to serve as a monitoring agent for segregating waste before it is collected from any health facilities. Additionally, the exchanged data from waste generator bins can inform collectors and other waste stakeholders about the waste's condition, potentially opening up opportunities for recycling companies to purchase used plastics or metals from hospital wastes. By implementing digitalization in medical waste management, waste segregation can improve, reduce the spread of diseases and injuries, and promote the recycling of hospital waste materials.
Keywords: Digitalization in waste management; Internet of things; IoT in waste management; Contemporary waste monitoring; IoT in medical waste management; Medical waste; Waste management; Waste segregation; 40 Engineering; 4011 Environmental Engineering; 12 Responsible Consumption and Production; 3 Good Health and Well Being